Mothers adhesion to nursing plan for irritant diaper dermatitis- an exploratory study - Ana Llonch Sabatés; Patricia Cristina Boscatto (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
This exploratory, descriptive, transversal, field study, which takes a quantitative approach, was carried out at a Family Health Unit in the municipal district of Francisco Morato, with the following objectives: to determine the knowledge, care actions and adhesion of mothers to nursing conducts to deal with irritant diaper dermatitis in their children; to identify the facilities and difficulties reported by the mother when carrying out the prescribed nursing conducts. The study population consisted of 29 mothers, and 29 children with irritant diaper dermatitis. The adhesion was classified as total, partial or non-existent. The results show that the majority of the mothers (58.8%) had no knowledge of irritant diaper dermatitis. As for the care actions to deal with their children's dermatitis, 93.1% of the mothers opted to use disposable diapers and 58.7% used a moist tissue when carrying out perineal hygiene, during diaper changes. In relation to the conditions of the child, the majority presented inadequate hygiene and hyperemia with skin peeling in the diaper region. It was determined that 65.6% of the mothers adhered to all the prescribed nursing conducts, 17.2% adhered only partially, and 17.2% did not adhere at all to the nursing conducts.